Stories of the unseen in authentic traditions - 'Umar S. 'Abdullah al-Ashqar; Shehded Fareh; Buslach, Denise J. (Amman, Jordan : Dar al-Nafaes, 2010)
Eschatology, Islamic; in the Hadith
English edition 1 (2010)
Includes hadith
Translated from Arabic edition 1 (2006)
Keywords: Hadith -- Texts; Hadith -- Criticism, interpretation, etc; Islamic eschatology in the Hadith